EFFECTIVE AND SUSTAINABLE SANITATION SYSTEM DEVELOPMENT PLAN FOR SLUM SETTLEMENTS IN TANJUNGBALAI CITY - Nella Febrina Silalahi; Cut Nuraini; Abdi Sugiarto (PT. Radja Intercontinental Publishing, 2025)
Sanitation issues in slum areas in Tanjungbalai City are a major concern in efforts to improve the quality of life and public health. This study aims to explore the factors that influence sanitation management in slum areas and provide policy recommendations to improve sanitation management. The research method used is a qualitative approach with data collection through interviews and field observations. The results of the study indicate that the main factors that hinder effective and sustainable sanitation management in slum areas are limited infrastructure, low community participation, and limited budget. In addition, the impact of poor sanitation on health and the environment is very significant, including increasing rates of water-based diseases and environmental pollution. The suggested policy recommendations include improving sanitation infrastructure, implementing environmentally friendly waste processing technology, empowering communities, and stricter law enforcement. Collaboration between the government, private sector, and communities is also needed to ensure the sustainability of sanitation programs in the future.